Designing a wireless sensor system for continuous monitoring of the cervical dilation of a pregnant woman. (29th June 2009) - Verma, Pramode; Ghosh, Anjan K.; Huck, Robert C.; Cheng, Samuel; Chen, Shanshan; Martens, Mark; Kaul, Anil
A novel electronic sensor system is designed to continuously monitor the dilation of the cervix of a pregnant female approaching labour and delivery. The system is capable of wirelessly transmitting the progress of dilation to a central monitoring agency that can get in touch with the attending physician and/or the hospital of the pregnant female. Using wireless telephony, the monitoring agency and/or the physician can advise the female about the medical care she needs at that moment, even though the female might be at her home or away from home, and away from the medical facility. This is an expanded version of a paper presented at the 3rd IEEE International Workshop on Medical Measurements and Applications, 9?10 May 2008, Ottawa, ON, Canada.